PERAN KEPALA DESA SEBAGAI PEMIMPIN DALAM MENEGAKKAN DISIPLIN KERJA PEGAWAI PADA KANTOR DESA TUHURAN KECAMATAN HAUR GADING KABUPATEN HULU SUNGAI UTARA (JAPB, 2022)
As a government leader at the lowest level, the village head has a very important role in directing and leading village officials and the people in the village towards successful development both morally and materially. However, until now some public opinion states that the village government is considered unable to serve the needs of the community optimally, this is because the village head in leading the implementation of village government is felt to be less assertive with regard to the discipline of village officials. In this study there were several problems related to employee work discipline, namely there were still employees who did not comply with the hours of entry and hours of return from work, this could be seen from employees who were often late to the office and employees who left before the time to go home from work. The purpose of this study was to find out how the role of the village head as a leader in enforcing employee work discipline at the Tuhuran Village Office, Haur Gading District, Hulu Sungai Utara Regency. This study uses a qualitative method. Data collection techniques used are observation, interviews, and documentation. The source of the data in this study was to take informants from 5 employees of the Tuhuran Village Office. The results showed that the role of the village head as a leader in enforcing employee work discipline at the Tuhuran Village Office, Haur Gading District, Hulu Sungai Utara Regency, played a significant role. Keywords: Role of Village Head, Leader, Work Discipline